SWOT ANALYSIS IN STRATEGIC MANAGEMENT: A CASE STUDY AT PURABAYA BUS STATION - Hening Widi Oetomo; Lilis Ardini (Universitas Hayam Wuruk Perbanas, 2012)
Gate automation (entrance automation) is a strategic plan that will be implemented at PurabayaBus Station Surabaya. An automation technique with Radio Frequency Identification(RFID) is a method that can be used to store or receive data remotely using RFID tags ortransponders. The purpose of this study was to determine the quadrant position in the SWOTdiagram of the gate automation plan and determine the most appropriate strategy in accordancewith the position of the quadrant on the SWOT diagram. Respondents who were usedto measure strengths and weaknesses included fifty employees of the Purabaya Bus StationSurabaya, while to measure opportunities and threats were fifty drivers and automotive businessmenwho currently use the bus station. Data were analyzed using SWOT in which thescores of internal factor (Internal Factor Analysis Summary-IFAS) and external factor (ExternalFactor Analysis Summary-EFAS) were calculated. The results showed that score ofinternal factor and external factor were greater than 2. Hence, the position of SWOT for thegate automation was located in quadrant 1, suggesting that a company has strength to takean advantage of the existing opportunities.